(untitled) (Jurnal Bahasa, 2021)
Legal Evidence of Criminal Intent is a detailed investigation of the evidence of malicious intent of an accused person. In court proceedings, the judge, prosecution and lawyers will use hedging language or cautious language to obtain evidence from the accused or witnesses who that can aid in determining the intent of the accused. This paper discusses the use of hedging language in courts for obtaining evidence from the accused and witnesses for the purpose of determining the intentions of the accused in the court trial. This case study used Grice’s (1975) Principles of Cooperation to analyse cross-examination data between the prosecution, prosecution witnesses and lawyers. The results of the study found that the use of hedging language or cautious language in court proceedings was when the legal and prosecution teams and witnesses responded to questions by the judge. Both parties use hedging language to respond politely. The study also found that the use of hedging language has a contribution in providing the meaning of evidence that demonstrate compliance in terms of maxim of quantity, maxim of quality, maxim of relation and maxim of manner, and can thus be classified as a proposition in legal submissions. These findings also highlight the polite responses of the prosecutors, lawyers and prosecution witnesses to the judge. Keywords: Criminal Intent legislation, hedging language, court process, Grice’s Principles of Cooperation (1975)